Washed microbiota transplantation improves sleep quality in patients with sleep disorder by the gut-brain axis - He, Hongxin; Li, Manqing; Qiu, Yifan; Wu, Zhiqing; Wu, Lei (Frontiers in Neuroscience, 2024)
Background The clinical impact of washed microbiota transplantation (WMT) from healthy donors in sleep disorder (SD) patients is unclear. This study aimed to investigate the effect of WMT in SD patients. Methods The clinical data were collected from patients with different indications receiving 1–3 courses of WMT, divided into two groups by 7 points of PSQI scale. The score of PQSI and SF-36 scale was used to assess the improvement in sleep quality and life quality among patients with sleep disorders following WMT. Finally, 16S rRNA gene amplicon sequencing was performed on fecal samples of patients with sleep disorders before and after WMT. Results WMT significantly improved sleep quality in patients with sleep disorder in the short and medium term. WMT significantly improved sleep latency, sleep time and total score in the short term. WMT significantly improved sleep quality and total score in the medium term. In terms of sleep quality and sleep latency, the improvement value also increased with the increase of treatment course, and the improvement effect of multiple treatment course was better than that of single and double treatment course. In the total score, the improvement effect of double and multiple treatment was better than that of single treatment. WMT also improved quality of life in the sleep disorder group. WMT significantly improved general health, vitality, social function and mental health in the short term. WMT significantly improved role-physical, general health, vitality, and mental health in the medium term. WMT regulated the disturbed gut microbiota in patients with sleep disorders. In the normal sleep group, WMT had no effect on the decline of sleep quality in the short, medium and long term, and had an improving effect on the quality of life. Conclusion WMT could significantly improve sleep quality and life quality in patients with sleep disorders with no adverse events. The improvement in sleep quality resulting from WMT could lead to an overall enhancement in life quality. WMT could be a potentially effective treatment for patients with sleep disorders by regulating the gut microbiota.